An agent model for the simulation of electrical vehicle charging management - Monteiro, Vítor Duarte Fernandes (2011)
This paper presents an agent model to the simulation of the charging process to control and monitor the Electric Vehicle charging process, taking into account the existing power distribution limitations. The process is based on the simulation study of the user consumption profile, based on two main steps: in the first step is performed the home consumption simulation by the data collection and the analysis of consumption of three family types (small, medium and large) and in the second step is the Electric Vehicle integration, using the identified profiles in low voltage. In this simulation we evaluate the limitations of the existing electrical power grid, and the factors that influence the EV charging. The main results obtained are the typical charging curves for residential consumption, which identify the power available for the Electric Vehicle charging, and determine the capability of the actual electrical power grid to supply energy to the final consumers and to charge the bank of batteries of the Electrical Vehicles, which can occur simultaneously.